2005
DOI: 10.1136/pgmj.2004.029512
|View full text |Cite
|
Sign up to set email alerts
|

Improving hospital doctors’ working lives: online questionnaire survey of all grades

Abstract: Background In 2001, the Department of Health produced the Improving Working Lives (IWL) for Doctors document. This is the first national survey which asks hospital doctors what changes are needed to improve their working lives. Methods An online questionnaire was run over a period of six weeks and was open to all doctors of all grades. Doctors were asked to choose their top five factors from a list of 35 diverse choices or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…Furthermore, it has been reported that doctors feel that better access to mentoring and clinical non-medical support would improve their working lives: 24 perhaps the support of pharmacists could improve these doctors' discomfort around prescribing. These non-medical mentors may also allow doctors to feel more comfortable asking for help, as we found that junior doctors were often reluctant to ask senior doctors for help.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that doctors feel that better access to mentoring and clinical non-medical support would improve their working lives: 24 perhaps the support of pharmacists could improve these doctors' discomfort around prescribing. These non-medical mentors may also allow doctors to feel more comfortable asking for help, as we found that junior doctors were often reluctant to ask senior doctors for help.…”
Section: Discussionmentioning
confidence: 99%
“…Working hours limitations as a result of EWTD have led to a loss of many surgical training opportunities, including elective operative time and, in this case, attendance on PTWRs. The effect of time limitation on training has also been seen in other specialties 14,16–18 …”
Section: Discussionmentioning
confidence: 84%
“…To our knowledge, there have been no previous studies that have looked specifically at education and training opportunities for SpRs. Trainees put an emphasis on such opportunities, as shown by the Intercollegiate Improving Working Lives (IIWL) survey, in which junior hospital doctors identified improved support for education and training as their first IWL choice 6 …”
Section: Discussionmentioning
confidence: 99%